STABILITY OF POLYCYCLIC AROMATIC HYDROCARBONS AND BENZOIC ACID DERIVATIVES UNDER SUBCRITICAL WATER CONDITIONS - Lindquist, Edward J. (East Carolina University, 2011)
The development of green environmental remediation, chromatography, and extraction techniques using subcritical water is the focus of our research group. The polarity of subcritical water can be manipulated by increasing its temperature in the range of 25 to 374 ºC while keeping it in the liquid state under moderate pressure. At elevated temperatures liquid water becomes less polar and behaves more like an organic solvent. The goal of this research is to determine the conditions under which certain polycyclic aromatic hydrocarbons (PAHs) and benzoic acid derivatives degrade in subcritical water. The stability of two PAHs (pyrene and naphthalene) and benzoic acid and three of its derivatives (anthranilic acid, syringic acid, and salicylic acid) under subcritical water conditions was investigated and the results are discussed in this thesis.  PAHs are pollutants widely formed as a result of incomplete combustion of organic materials. The effects of temperatures ranging from 200 to 350 ºC and heating times of 30 and 300 min on the degradation of pyrene and naphthalene in solutions of water and 3% hydrogen peroxide were determined. Our results show that PAHs can be degraded under subcritical water conditions, and thus, this technique may be applied to the environmental remediation of these pollutants.  Benzoic acid and its derivatives are found in medicinal herbs and other plants. While the extraction of these active ingredients from herbs using subcritical water is non-toxic and preferred, the decomposition of these compounds under subcritical water conditions has to be examined. The stability studies of this group of analytes were carried out at temperatures ranging from 50 to 250 ºC with heating times of 10 and 30 min. The degradation of the benzoic acid derivatives increased with rising temperature and additional heating time. The degradation products of benzoic acid and the three derivatives were identified and quantified by high performance liquid chromatography (HPLC) and confirmed by gas chromatography/mass spectrometry (GC/MS). Under subcritical water conditions anthranilic acid, syringic acid, salicylic acid, and benzoic acid underwent decarboxylation to form aniline, syringol, phenol, and benzene, respectively.
Keywords: Chemistry, Analytical; Benzoic acid and derivatives; Degradation; Stability; Subcritical water; Analytical chemistry; Polycyclic aromatic hydrocarbons; Benzoates; Environmental chemistry; Chromatographic analysis; Extraction (Chemistry)